2002
DOI: 10.1182/blood.v100.2.721
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the hematopoietic potential of muscle-derived cells in mice

Abstract: Cells in murine muscle have been reported to differentiate into hematopoietic stem and progenitor cells and thus repopulate the hematopoietic system of an irradiated animal. This activity was attributed to muscle stem cells. We used an in vitro and in vivo approach to identify the hematopoietic repopulating activity found in muscle tissue of mice by antibody staining and cell sorting. We confirmed existence of a hematopoietic repopulating cell in muscle tissue, but the data strongly suggest that repopulation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 12 publications
1
31
0
Order By: Relevance
“…This explains, for example, why heterogeneous populations of stem cells could also be detected in various organs (eg HSC in muscle tissue). [59][60][61][62] …”
Section: Evidence That Tissue Damage Triggers Circulation Of Tcscmentioning
confidence: 99%
“…This explains, for example, why heterogeneous populations of stem cells could also be detected in various organs (eg HSC in muscle tissue). [59][60][61][62] …”
Section: Evidence That Tissue Damage Triggers Circulation Of Tcscmentioning
confidence: 99%
“…However, later studies demonstrated that muscle-derived cells with hematopoietic activity were resident HSCs and not muscle cells that had transdifferentiated in response to hematopoietic signals (McKinney-Freeman et al, 2002;Geiger et al, 2002;Issarachai et al, 2002). Nevertheless, if it were possible to maintain and expand human HSCs from muscle, muscle biopsies could provide an alternative source of HSCs for clinical transplantation.…”
Section: Evidence For and Against Lineage Promiscuity By Adult Stem Cmentioning
confidence: 99%
“…These cells have been shown to give rise to long-term hematopoiesis [2], and their ability to generate hematopoietic cells in at least three generations of lethally irradiated recipients for more than 1 year suggests a selfrenewal ability [3]. The contamination of muscle tissue by a circulating stem cell has been suggested as a possible explanation for this phenomenon [5], but the transplantation of many nucleated blood cells did not yield any survival in irradiated mice [5,8,9]. The current hypothesis is that there is a hematopoietic cell niche in the muscle tissue that is either of post-natal or embryonic origin.…”
Section: Introductionmentioning
confidence: 99%